Regulation of ferritin and heme oxygenase synthesis in rat fibroblasts by different forms of iron. - Eisenstein, R S (1991)
Synthesis of the iron-storage protein ferritin is thought to be regulated at the translational level by the cytosolic content of chelatable iron. This response to iron is regulated by the iron-modulated binding to ferritin mRNAs of a repressor protein, the iron regulatory element-binding protein. From measurements made in a cell-free system, regulation of the iron regulatory element-binding protein has been recently suggested to involve direct interaction with hemin. The following observations on the synthesis of ferritin and of heme oxygenase (HO), the heme-degrading enzyme, in rat fibroblasts or hepatoma cells lead us to conclude that chelatable iron is a direct physiological regulator of ferritin synthesis in intact cells: (i) the inhibitor of heme degradation, tin mesoporphyrin IX, reduces the ability of exogenous hemin to induce ferritin synthesis but enhances HO synthesis; (ii) the iron chelator desferal suppresses the ability of hemin to induce synthesis of ferritin but not of HO; (iii) the heme synthesis inhibitor succinylacetone does not block iron induction of ferritin synthesis; (iv) there is no apparent relationship between the ability of various metalloporphyrins to inactivate the iron regulatory element-binding protein in cell-free extracts and their capacity to induce ferritin synthesis in intact cells; (v) administered inorganic iron significantly induces the synthesis of ferritin but not of HO; (vi) addition of delta-aminolevulinic acid to stimulate heme synthesis represses the ability of inorganic iron to induce ferritin synthesis while activating HO synthesis. Taken together, our results demonstrate that (i) release of iron by HO plays an essential role in the induction of ferritin synthesis by heme and (ii) chelatable iron can regulate ferritin synthesis independently of heme formation.